Mercury-Mediated Cross-Resistance to Tellurite in Pseudomonas Spp. Isolated from the Chilean Antarctic Territory - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Diaz, P; Díaz-Vásquez, W (Royal Society of Chemistry, 2016)
Mercury salts and tellurite are among the most toxic compounds for microorganisms on Earth. Bacterial mercury resistance is established mainly via mercury reduction by the mer operon system. However, specific mechanisms underlying tellurite resistance are unknown to date. To identify new mechanisms for tellurite detoxification we demonstrate that mercury resistance mechanisms can trigger cross-protection against tellurite to a group of Pseudomonads isolated from the Chilean Antarctic territory. Sequencing of 16S rRNA of four isolated strains resulted in the identification of three Pseudomonads (ATH-5, ATH-41 and ATH-43) and a Psychrobacter (ATH-62) bacteria species. Phylogenetic analysis showed that ATH strains were related to other species previously isolated from cold aquatic and soil environments. Furthermore, the identified merA genes were related to merA sequences belonging to transposons commonly found in isolated bacteria from mercury contaminated sites. Pseudomonas ATH isolates exhibited increased tellurite resistance only in the presence of mercury, especially ATH-43. Determination of the growth curves, minimal inhibitory concentrations and growth inhibition zones showed different tellurite cross-resistance of the ATH strains and suggested a correlation with the presence of a mer operon. On the other hand, reactive oxygen species levels decreased while the thiol content increased when the isolates were grown in the presence of both toxicants. Finally, qPCR determinations of merA, merC and rpoS transcripts from ATH-43 showed a synergic expression pattern upon combined tellurite and mercury treatments. Altogether, the results suggest that mercury could trigger a cell response that confers mercury and tellurite resistance, and that the underlying mechanism participates in protection against oxidative damage. © The Royal Society of Chemistry.